Internal Auditor Professionalism: Determinants and Its Effect on Behavior Auditor Ethics - Novien Rialdy; Maya Sari; Syafrida Hani; Jufrizen Jufrizen; Irfan Irfan (Integrated Journal of Business and Economics (IJBE), 2023)
This study aims to study the factors that influence the Professionalism and Ethical Behavior of Auditors at BPKP North Sumatra and produce a model of Mediation of Professionalism on the Influence of Moral Intensity and Religiosity on Auditor Ethical Behavior at BPKP North Sumatra. This research is basic (basic research). The strategy employs a quantitative approach. The sample includes all BPKP North Sumatra internal auditors. Using a technique called "saturated sampling," criteria from all internal auditors were used as samples. One hundred forty-three internal auditors were chosen as the final sample. The method used is Partial Least Square (PLS). The results showed that moral intensity has a positive effect on internal auditor professionalism, religiosity has a positive effect on internal auditor professionalism, moral intensity has a positive effect on ethical decision making, religiosity has a positive effect on ethical decision making, Internal Auditor professionalism has a positive effect on ethical decision making, the moral intensity does not have a significant effect on ethical decision making through Internal Auditor Professionalism and religiosity does not have a significant effect on ethical decision making through Internal Auditor Professionalism